2018
DOI: 10.1287/stsc.2018.0062
|View full text |Cite
|
Sign up to set email alerts
|

Strategy and the Institutional Envelope

Abstract: Classical approaches to strategy are built around two dominant pillars to explain firm performance: industry structure and firm strategy and capabilities. Firm performance is typically seen as a result of a "fit," or complementarity, between industry structure and firm strategic choices. We supplement the classical model of strategy with a third pillar, that of the institutional envelope. We argue that the institutional envelope, as its name suggests, is a pervasive influence on the strategy-performance relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Whereas H1 predicts a positive impact of family influence on firm growth, the institutional environment may have an important moderating effect. This is in line with the prior research that has emphasized the theoretical and practical importance of institutional environments for family firm decision-making processes (Ahuja et al, 2018; Banalieva et al, 2015; North, 1990; Peng & Jiang, 2010).…”
Section: Theory and Hypotheses: Current Control Versus Transgenerational Controlsupporting
confidence: 90%
“…Whereas H1 predicts a positive impact of family influence on firm growth, the institutional environment may have an important moderating effect. This is in line with the prior research that has emphasized the theoretical and practical importance of institutional environments for family firm decision-making processes (Ahuja et al, 2018; Banalieva et al, 2015; North, 1990; Peng & Jiang, 2010).…”
Section: Theory and Hypotheses: Current Control Versus Transgenerational Controlsupporting
confidence: 90%
“…In such contexts, effectual entrepreneurs can better cope with institutional uncertainty by means of co-creation with important stakeholders. The findings in relation to industrial and market moderators are relevant to the strategy tripod literature, which has suggested that the effectiveness of corporate strategies is constrained by industrial competition and institutional infrastructure (Ahuja et al , 2018; Peng et al , 2009). In particular, studies of effectuation should consider industrial and market context, beyond specific organizational and entrepreneurial characteristics.…”
Section: Discussionmentioning
confidence: 84%
“…Departing from existing research, our study points out that noncontrolling ownership stakes by foreign institutional investors may indirectly shape firms' CPS through intensifying these firms' political dependence. Finally, at a broader level, our study contributes to a growing call for better understanding of how firms shape their environments (Ahuja, Capron, Lenox, & Yao, 2018). Prior research has focused on the actions of shaping (Gavetti et al, 2017); our study helps unpack some of its antecedents.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, at a broader level, our study contributes to a growing call for better understanding of how firms shape their environments (Ahuja, Capron, Lenox, & Yao, 2018). Prior research has focused on the actions of shaping (Gavetti et al, 2017); our study helps unpack some of its antecedents.…”
Section: Discussionmentioning
confidence: 89%